Optimization of shielded metal arc welding process parameters on weld bead geometry using Jaya algorithm and Firefly algorithm - Pushp Kumar Baghel (Advances in Mechanical Engineering, 2025)
The foremost aspect in welding is to improve the mechanical and microstructural properties in the weldment. The properties depend upon the weld bead characteristics. This is in turn depend upon the welding process. Shielded Metal Arc welding (SMAW) is the welding process which is simpler, usable and robust in nature. The bead characteristics such as bead width (BW), reinforcement ( R ), penetration ( P ), weld penetration shape factor (WPSF), weld reinforcement form factor (WRPF) has been selected as output weld characteristics which are influenced by parameters such as welding current ( I ), welding speed ( S ), arc length ( A ), electrode advance angle €, and joint gap ( G ). In this paper a response surface methodology is implemented which predicts the optimum results of 0.51% error from the observed results. To find the optimum results metaheuristic algorithms that is, Jaya (JA) algorithm and Firefly (FA) algorithm was implemented. The results obtained are within the maximum and minimum permissible limits and of 0.22% and 0.31% deviation from the observed values. This shows the accuracy and refinement of results using algorithms. The real world verification is done from the regression model. The sensitivity analysis and parameter effect to show variation in parameters influence the results has been presented.